Analytical methods for stress-crack width relationship and residual flexural strengths of 3D/4D/5D steel fiber reinforced concrete. (5th September 2022) - Ding, Chong; Gao, Danying; Guo, Aofei
Highlights: Integration by substitution for closed form solutions of flexural beam was modified. Three-point bending, uniaxial tensile and fiber pullout tests were employed. A unified expression of maximum pullout force for fiber with i hooks was proposed. σ - w relationships in polylinear and polynomial forms were acquired by proposed methods. Residual flexural strengths were predicted by analytical and semi-analytical methods. Abstract: In this study, three methods were proposed to predict the stress-crack width ( σ - w ) relationship and the residual flexural strengths of 3D/4D/5D steel fiber reinforced concrete (SFRC): (1) the integration by substitution was firstly modified to derive the closed-form solutions for flexural beam, and then the polylinear σ - w relationship was achieved through the inverse analysis method; (2) the polynomial σ - w relationship was proposed according to the fiber pullout test (FPT) and a regression analysis method; (3) a semi-analytical method for the residual flexural strengths was established according to the three-point bending test (3PBT), polynomial σ - w relationship and regression analysis. Finally, 24 groups of specimens with varying fiber types (3D, 4D and 5D) and fiber volume fractions (0.5%, 1.0% and 1.5%) were manufactured for 3PBT, UTT and FPT to verify the proposed three methods. Results showed that the proposed methods could effectively predict the σ - w relationship and the residual flexural strengths of SFRC, and could be widely used in structural analysis and design.